Analisis Kepatuhan Berobat Hipertensi ditinjau dari Fungsi Pemeliharaan Kesehatan Keluarga dan Respon Spiritual di desa Kadungrejo Baureno Bojonegoro - Abidin, Ahmad Zainal (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2023)
Unknowingly developing into a condition that can lead to major illnesses and have a big impact on everyone's health, hypertension (HT) is a degenerative disease that results from anomalies in blood vessel flow (Udjianti, 2012). This condition is brought on by living an unhealthy lifestyle, treating hypertension improperly or completely, and other co-morbidities that raise the state of hypertension. This study's goal was to examine how religious response and family health were maintained by adherence to hypertension therapy in Kadungrejo Baureno Village, Bojonegoro. This study's design employs cross sectional analysis utilizing observational data. 72 persons made up the study's total population, while 61 respondents made up the sample. According to the study's findings, adherence to treatment among hypertension patients is moderate, with 33 respondents (54.1%), the role of maintaining family health among hypertension patients is moderate, with 40 respondents (65.6%), and the spiritual response among hypertension patients is quite positive, with 36 respondents (59.0%). Based on the ordinal regression test's findings, the value was 0.000 (<0,05), has a wald score of 15,263 for the spiritual response and 133,754 for the family health maintenance function. According to the study's findings, there is a significant correlation between hypertension patients' adherence to treatment and their ability to preserve their family's health as well as their spiritual reactions in the hamlet of Kadungrejo Baureno Bojonegoro.